Lung Adenocarcinoma With Initially Co‐Occurring EGFR and BRAF Double Mutation: A Case Report and Literature Review - Lu Wang; Xueting Wang; Motong Xu; Yanan Wang; Lingxin Feng; Xue Yang; Jing Wang (Thoracic Cancer)
ABSTRACT Vrafmurine sarcoma viral oncogene homolog B (BRAF) mutations, including both V600E and non‐V600E variants, are infrequent in non‐small cell lung cancer (NSCLC), representing approximately 2% of lung adenocarcinomas. Activated BRAF mutations are regarded as an underappreciated oncogenic driver in NSCLC, typically occurring in a mutually exclusive manner with epidermal growth factor receptor (EGFR) mutations, as well as ALK and ROS1 rearrangements. In recent years, advancements in multiple‐gene panel testing have demonstrated that EGFR mutations and BRAF mutations can coexist. Notably, the secondary BRAF V600E mutation has been identified as one of the mechanisms contributing to resistance against EGFR tyrosine kinase inhibitors (TKIs) in EGFR‐mutated lung adenocarcinomas. However, the role of co‐occurring BRAF mutations and associated treatment strategies in patients with EGFR mutations has not been thoroughly investigated. Additionally, the profile of adverse events related to combination therapy has not been previously evaluated. This case report presents a patient with co‐occurring EGFR and BRAF mutations who demonstrated a sustained response and tolerance to adverse events when treated with a combination of Osimertinib, Trametinib, and Dabrafenib.